The stress test, differences in the physiological response between sedentary and recreational athletes - Hernández-Pacheco, Guadalupe; Cano, Víctor; Armendáriz-González, Gilberto; Valencia-Cañedo, Cesar A; Martínez- Rosas, Martín (Horizonte Sanitario, 2025)
Objective: Compare the physiological response between sedentary and recreational athletes during the stress test.Materials and Methods: An analytical cross-sectional study was carried out; sedentary male volunteers and recreational athletes were included. A stress test was performed with the modified Bruce protocol on a ramp. Statistical analysis. A descriptive analysis of the variables was carried out, and the difference between groups was evaluated usingthe t-test and the nonparametric Wilcoxon and Kruskal-Wallis tests. The value of p